SMOTE-Tomek Re-sampling Based on Random Forest Method to Overcome Unbalanced Data for Multi-class Classification - Shabrina Assyifa, Dhiaka; Luthfiarta, Ardytha (Inform : Jurnal Ilmiah Bidang Teknologi Informasi dan Komunikasi, 2024)
Mobile app review data needs to be utilized to understand the app characteristics desired by users. App providers can improve app performance based on user preferences by using sentiment and emotion classification on app review data. However, problems that often arise in text-based analysis are data variation and data imbalance. This can lead to biased and inaccurate classification models. It is necessary to perform pre-processing to comprehend the data requirements and implement feature extraction for word weighting to overcome the variation in the data. In addition, re-sampling techniques are also needed to overcome the imbalance in sample distribution. Re-sampling techniques such as Tomek Links and SMOTE only focus on majority or minority data. This research applies the SMOTE-Tomek merging technique, aiming at not only the minority data but also the majority data. The model performance becomes better because the technique combines oversampling and under-sampling of the majority of data to eliminate the noise of data. The data was modeled using an Ensemble Learning Random Forest for classification. The model performance resulted in a Precision value of 84%, Recall of 84%, F1-Score of 84%, and Accuracy of 84%. Furthermore, the model was optimized using GridSearchCV and obtained an increase in Precision 85%, Recall 85%, F1-Score 85%, and Accuracy 85%.